Relasi Kuasa dan Dinamika Isi Media Studi Ekonomi Politik Komunikasi Media Online Kompas.com Dan JawaPos.com - Sayyidah; Nurikhsan Aldi Perdana; Muhammad Qori Qordofa; Naila Mafayiziya Hayat (AL-MUNAWWIR: Jurnal Komunikasi, Pendidikan, & Syari'ah, 2026)
This research aims to describe the dynamics of state power in the production of information in the Kompas.com and Jawapos.com media on the results of the presidential candidate 2024 survey. This research uses a qualitative approach, qualitative is supported by an understanding of the facts of the inductive thinking process, namely thinking that refers to individual phenomena to produce conclusions or inferences. The informants amounted to three people who were selected purposively. Data validity testing was carried out through source triangulation techniques. Data collection techniques were conducted through interviews, observation, and literature study. The results of this study show how the production of Kompas.com and JawaPos.com power relations affects the dynamics of news content. There is intervention from capital and media owners and power in determining the theme and content of the news through headlines or news intensity. Comparison of Power Relations and Media Content Dynamics in the Study of the Political Economy of Online Media Communication Kompas.com and JawaPos.com in Reporting the Results of the 2024 Presidential Candidate Survey. Kompas.com and JawaPos.com do Commodification and Spaliasation. with the combination of Commodification and Spatialization carried out by Kompas.com and JawaPos.com, it finally gave rise to the Structuration of structured iedological equalization in media corporations. Political economy and power relations are two things that are mutually sustainable and played appropriately as a media corporation to be able to maintain existence in competition between media.